Calculative culture in management control systems: scale and typology development. Issue 2 (2nd April 2020) - Marc, Mojca; Peljhan, Darja
ABSTRACT: A calculative culture (CC) conveys the way managers use analytical models and numbers for decision-making. We investigate whether this concept holds the potential to become a contextual variable in research on Management Control Systems (MCS) because CC arguably relates to the design and use of MCS, and to organisational performance. Using a mixed methods approach (literature review, interviews, a cross-sectional survey, confirmatory factor analysis-CFA), we develop and validate an instrument for measuring CC as a group-level variable. We find CC has two dimensions: (1) analytical enthusiasm (enthusiasm for advanced analytical methods); and (2) numerical pragmatism (pragmatism in number interpretation). We characterise four types of CC found in top management teams: (1) smart enthusiasts; (2) extreme sceptics; (3) irrational sceptics; and (4) extreme enthusiasts. Finally, we empirically confirm that CC acts independently alongside other contextual variables, such as size, age, industry, ownership structure, strategy type, (geographic) market orientation, perceived organisational performance relative to competitors, and business environment uncertainty. This shows CC may be employed as an additional contextual variable in future studies on MCS design and use.